Oral Health Policies to Tackle the Burden of Early Childhood Caries: A Review of 14 Countries/Regions - Jieyi Chen; Duangporn Duangthip; Sherry Shiqian Gao; Fang Huang; Robert Anthonappa; Branca Heloisa Oliveira; Bathsheba Turton; Callum Durward; Maha El Tantawi; Dina Attia; Masahiro Heima; Murugan Satta Muthu; et al. (Frontiers Media S.A., 2021)
Aim: Early childhood caries (ECC) has significant public health implications but has received inadequate global attention. There is limited information regarding the success of oral health policies implemented to address the challenges of ECC. This review aimed to summarize such policies to tackle ECC from different countries/regions.Method: Independent collaborators from 14 countries/regions (Australia, Brazil, Cambodia, China, Hong Kong, Egypt, India, Indonesia, Japan, Nigeria, Thailand, UK, USA, and Venezuela) collected the data. The ECC status, dental workforce, oral health policies on ECC prevention in different countries/regions were summarized by each country.Results: The findings indicated that ECC prevalence varied in different countries/regions. The lowest prevalence of ECC among 5-year-old children was found in Nigeria (7%), and the highest was found in Indonesia (90%). The existing dental workforce and resources are limited in most countries. The smallest dentist to population ratio was reported by Nigeria at 1:48,400, whereas the highest ratio was in Brazil (1:600). Out of 14, three (21%) countries namely India, Venezuela and Cambodia had no national oral health policies addressing ECC and four (29%) countries (Cambodia, China, India, Venezuela) had no publicly funded dental care program for 0-5-year-old children. Water fluoridation is available in four countries/regions (Australia, Brazil, Hong Kong, USA).Conclusion: ECC remains a global health challenge and dental workforce is limited. National/regional programs to tackle ECC are not yet prioritized in many countries/regions. Evidence to support demonstration projects is limited. Further research on the cost-effectiveness of interventions strategies is required for policymakers.